Digital Misinformation in Aesthetic Dermatology: The Role of Social Media and Generative Artificial Intelligence in Shaping Patient Safety, Trust, and Evidence-Based Practice: A Narrative Review (2022–2026) - Marusza, Michal; Krupski, Aleksander; Stielow, Victoria; Zatyka, Antonina (Quality in Sport, 2026)
Social media and generative artificial intelligence (AI) are increasingly impacting how patients access, interpret and apply information related to aesthetic dermatology. Both technologies offer an additional medium for education about aesthetic dermatology but have the potential to magnify the impact of misleading and/or incomplete risk disclosure, commercialism, idealized representations of physical beauty and persuasive but unreliable advice. Purpose: This is a narrative literature review of how digital misinformation can affect the safety of patients, the relationship between patients and physicians and evidence-based practices in the field of aesthetic dermatology. Methodology: The research employed a systematic search strategy using the MEDLINE/PubMed database along with the Scopus database. In addition, reference screening was performed manually of all peer-reviewed English language publications identified as relevant to this topic, which were published between January 1, 2022 and March 23, 2026. Due to the variability of the evidence, the studies were synthesized by themes rather than quantitative synthesis. Conclusion: Results indicate that aesthetic dermatology is uniquely vulnerable to misinformation due to the visual persuasion and consumer behavior that influences patient demand for services, patient perceptions of attractiveness and social norms of beauty that are established on platforms. Additionally, social media provides a platform for content that is emotionally provocative and commercially viable, while generative AI enables scalable creation of believable text and synthetic images. As such, both social media and generative AI may generate unrealistic expectations among patients, create barriers to informed consent, undermine the calibration of trust and influence clinical decision-making.